Fetal and neonatal outcomes in intrahepatic cholestasis of pregnancy - Sharma, Parul; Sarkar, Bani; Majhi, Bangali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrahepatic cholestasis of pregnancy has been associated with adverse fetal and neonatal outcomes. The objective of this study was to assess the improvement in fetal and neonatal outcomes with timely intervention in pregnant females with intrahepatic cholestasis of pregnancy Methods: This prospective observational study included 50 patients attending antenatal clinic of the Department of Obstetrics and Gynecology of Dr. RML Hospital, from 1st November 2015 to 31st March 2017, using inclusion and exclusion criteria. History, examination, blood investigations, with ultrasound upper abdomen was done for all the patients. Diagnosed patients were treated accordingly and fetal and neonatal outcomes were studied. The data was analyzed using STATA (version 13.1, Stata Corp 4905 Lakeway Drive College Station, Texas 77845 USA). Comparisons were analyzed using Chi-Square, Student’s t-tests. Results: In the present study, in view of timely diagnosis and intervention, 82% of the neonates had birth weight >2.5kg. 94% of the total neonates had >7 APGAR at 1min, and 100% of the neonates had >7 APGAR at 5min. No stillbirth was observed in present study group. No NICU admission was observed in the present study. Conclusions: Patients with intrahepatic cholestasis of pregnancy should be taken with utmost care. With early intervention, the adverse effects on fetus and neonates can be reduced to a significant amount.